ANALYSIS OF APPROACHES ADMINISTRATION OF ACADEMIC SERVICES TO SOCIETY OF AUTONOMOUS HIGHER EDUCATION INSTITUTIONS USING SYSTEM THEORY - Sukeevong, Watcharapong; Chirinang, Pensri; Chaisakulkiet, Udomvit; Mankan, Wiphat (Journal of MCU Nakhondhat, 2024)
This academic article aims to explain and Analysis of approaches administration of academic services to society of autonomous higher education institutions using systems theory. Which discusses the meaning and importance of academic service to society Analysis of the administration of academic services to society of autonomous higher education institutions. and approaches administration of academic services to society of autonomous higher education institutions using systems theory. By showing the meaning and importance of academic service administration to society. Analyzing the administration of academic services to society increases the opportunity for operations to be consistent with changes in the environment that meet the needs of communities and society in the area. And promote approaches for becoming an important source of income for higher education institutions. This academic article also suggests approaches for the administration of academic services to society of autonomous higher education institutions using system theory. That can support academic services to society in new ways. Meets the needs of the community and society. Autonomous higher education institutions should have management approaches that emphasize efficiency in every step. By applying modern management principles to the administration of academic services to society. Management is like a living thing that must be influenced by the organizational environment according to systems theory. Consists of 1) Input factors including policy, personnel, budget, materials and equipment. 2) Process aspect includes operational planning, management, budget, achievement oriented, monitoring and evaluation 3) Productivity aspect includes evaluation of agency performance. And you can bring the data back to every step when you want to improve or add to the process to be more complete. The important thing should be to consider the environment. This refers to the recipient of academic services so that the administration meets the set goals and achieve maximum efficiency.